Remember the alamo [videorecording (DVD)]. (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
"In the early 1830s Texas was about to explode. Although under Mexican rule, the region was home to more than 20,000 U.S. settlers agitated by what they saw as restrictive Mexican policies. Mexican officials, concerned with illegal trading and immigration in Texas, were prepared to fight hard to keep the province under their control. Caught in the middle were the area's 4,000 Mexican Texans or Tejanos who were forced to choose a side. The conflict pitted brother against brother and devastated the community. This film shows the Tejano gamble for a more prosperous future in an independent Texas proved tragic."